OMALIZUMAB FOR CHILDREN WITH BRONCHIAL ASTHMA: INDICATIONS TO APPLICATION - T.V. Kulichenko (Педиатрическая фармакология)
Antibodies to IgE are a totally new class of medications currently used to enhance the supervision over severe persistent atopic bronchial asthma. Omalizumab is the most well studied, first and only medication of this group, which is recommended for the application and is allowed for treatment of uncontrolled bronchial asthma among adults and children aged 12 and over in different countries of the world, including Russia. High omalizumab assisted treatment costs, as well as the need in the monthly visits to the doctor for the omalizumab injections are justified for the patients, requiring repeat hospitalizations, emergency medical aid, using high doses of the inhalation and/or systemic glucocorticosteroids. The article reviews the criteria for the selection of patients fit for omalizumab assisted treatment.Key words: omalizumab, anti-ige-antibodies, bronchial asthma, allergic rhinitis, treatment, children.